All Days 2004
DOI: 10.4043/16089-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mad Dog Project: Regulatory Approval Process for the New Technology of Synthetic (Polyester) Moorings in the Gulf of Mexico

Abstract: This paper summarizes the responsibilities between the Minerals Management Service (MMS), United States Coast Guard (USCG), the American Bureau of Shipping (ABS), and BP Exploration & Production, Inc. (BP) as the Operator for gaining regulatory approval on the new technology of synthetic (polyester) moorings. More specifically, the Mad Dog Project received the first approval for the permanent use of polyester moorings in the Gulf of Mexico. Authors present the regulatory strategy and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Synthetic fibre rope moorings have many advantages over traditional chain including: lower stiffness and greater extension properties which can lead to reduced mooring and anchoring loads (Johanning et al, 2007); they are often lighter and therefore easier and cheaper to handle and deploy (Ridge et al, 2010); this reduced weight can have causal effects, reducing the load on the floating body and thus leading to further optimisation of the floater itself and other subsystems (Gordelier et al, 2018); the adoption of synthetics also avoids the corrosion risk evident with steel chain that has led to multiple premature mooring failures (Ma et al, 2013). Whilst historically offshore oil and gas adopted steel chain mooring systems, in order to facilitate exploration into ever deeper waters the adoption of synthetic mooring systems is now common (Bugg et al, 2004). Despite early concerns on fatigue performance, Banfield et al (1999) demonstrated that polyester rope is suitable for deep-water moorings with lifetimes exceeding 20 years, having a fatigue performance comparable to spiral strand steel wire rope.…”
Section: Synthetic Ropesmentioning
confidence: 99%
“…Synthetic fibre rope moorings have many advantages over traditional chain including: lower stiffness and greater extension properties which can lead to reduced mooring and anchoring loads (Johanning et al, 2007); they are often lighter and therefore easier and cheaper to handle and deploy (Ridge et al, 2010); this reduced weight can have causal effects, reducing the load on the floating body and thus leading to further optimisation of the floater itself and other subsystems (Gordelier et al, 2018); the adoption of synthetics also avoids the corrosion risk evident with steel chain that has led to multiple premature mooring failures (Ma et al, 2013). Whilst historically offshore oil and gas adopted steel chain mooring systems, in order to facilitate exploration into ever deeper waters the adoption of synthetic mooring systems is now common (Bugg et al, 2004). Despite early concerns on fatigue performance, Banfield et al (1999) demonstrated that polyester rope is suitable for deep-water moorings with lifetimes exceeding 20 years, having a fatigue performance comparable to spiral strand steel wire rope.…”
Section: Synthetic Ropesmentioning
confidence: 99%
“…Polyester fibre ropes have been used for mooring deep-water offshore platforms for many years now (De Pellegrim, 1999;Bugg, 2004;Haslum, 2005) and extensive fatigue testing has shown that their fatigue performance is better than equivalent steel components (Banfield, 2000). The idea of using nylon ropes for long-term mooring lines is relatively new as there is little available knowledge on the durability behaviour of such structures.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic fibre ropes were proposed for deep-water moorings of floating offshore oil and gas platforms by Del Vecchio nearly 30 years ago [1], and are now widely accepted [2,3]. The low linear density of polyester fibre ropes compared to steel wire and chain has made them the preferred choice beyond 1500 m depth.…”
Section: Introductionmentioning
confidence: 99%